2020
DOI: 10.14414/jbb.v10i1.2292
|View full text |Cite
|
Sign up to set email alerts
|

Leverage dan Profitabilitas dalam Memprediksi Financial Distress Perusahaan Pertambangan Periode 2016-2018

Abstract: Financial distress merupakan suatu kondisi di mana sebuah perusahaan mengalami kesulitan keuangan. Adanya fenomena perusahaan yang ter-delisting dari Bursa Efek Indonesia menjadi dasar untuk mengkaji ulang model prediksi kesulitan keuangan yang tepat. Penelitian ini bertujuan untuk memberikan bukti secara empiris mengenai pengaruh leverage dan profitabilitas dalam memprediksi financial distress. Sampel penelitian  diperoleh dengan menggunakan metode purposive sampling. Sampel penelitian yang memenuhi kriteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
1
2
1
Order By: Relevance
“…These results are in line with research conducted by Dirman (2020), Wulandari &Fitria (2019), andSucipto &Muazaroh (2017) which shows that the leverage ratio has no effect on Financial Distress. This result is different from research conducted by Giovanni et al, (2020), Septiani &Dana (2019), andNindita et al, (2014) which showed that the leverage ratio had a significant negative effect on Financial Distress, and was different from research conducted by Agustini & Wirawati (2019) and Hidayat & Meiranto (2014) which shows that the leverage ratio has a significant positive effect on Financial Distress.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…These results are in line with research conducted by Dirman (2020), Wulandari &Fitria (2019), andSucipto &Muazaroh (2017) which shows that the leverage ratio has no effect on Financial Distress. This result is different from research conducted by Giovanni et al, (2020), Septiani &Dana (2019), andNindita et al, (2014) which showed that the leverage ratio had a significant negative effect on Financial Distress, and was different from research conducted by Agustini & Wirawati (2019) and Hidayat & Meiranto (2014) which shows that the leverage ratio has a significant positive effect on Financial Distress.…”
Section: Discussioncontrasting
confidence: 89%
“…These results are in line with research conducted by Agustini & Wirawati (2019), Wulandari &Fitria (2019), andSucipto &Muazaroh (2017) which showed that the profitability ratio had a significant negative effect on Financial Distress. This result is different from the research conducted by Giovanni et al, (2020) and Dirman (2020) which showed that the profitability ratio had a significant positive effect on Financial Distress, and there were different results from the research conducted by Nindita et al, (2014) and Hidayat & Meiranto (2014)which state that the profitability ratio has no effect on Financial Distress. The activity ratio is the ratio used to measure the effectiveness of the utilization of the company's resources.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Rumus untuk menghitung nilai Z score untuk model Altman Z-Score. Sumber dari penelitian (Giovanni, Utami, & Yuzevin, 2020), yaitu: Z= 1,2X1 + 1,4X2 + 3,3X3 + 0,6X4 + 1,0X5 Keterangan: X1 = modal kerja/total asset X2 = laba ditahan/total asset X3 = Penghasilan sebelum bunga dan pajak/total asset X4 = nilai pasar ekuitas/nilai buku total liabilitas X5 = penjualan/total asset Profitabilitas adalah kondisi dimana perusahaan mampu menghasilkan laba atau profit dalam suatu periode yang dinyatakan dalam bentuk persentase. Semakin tinggi tingkat profitabilitas perusahaan berarti semakin tinggi kemampuan perusahaan dalam menghasilkan laba.…”
Section: Studi Literaturunclassified
“…Financial reports offer insights into financial statements, cash flows, and financial performance. To make this information useful, the profit figure must be predictive, variable, and persistent (Giovanni et al, 2020;Hery, 2015;Murhadi, 2013;Prihadi, 2019).…”
Section: Veronica Sonia Kinanti Muhyarsyahmentioning
confidence: 99%